Peer effects and intentional entrepreneurial behaviour: a systematic literature review and research agenda - Portyanko, Sergey; Reinmoeller, Patrick; Hussels, Stephanie; Turner, Neil (Wiley, 2022)
What role peers play in individuals’ decisions to become entrepreneurs and to what extent peer effects play a role in influencing behaviours at the various stages of business venturing are important questions for scholars and policymakers. This systematic review takes stock of the recent additions to the literature around the phenomenon of peer influence in entrepreneurship. The review identified 2894 documents which were then narrowed down through three consecutive filtering stages. We thematically analysed the final sample of 27 empirical studies that shed light on how individual peers influence the process and outcomes of these individuals’ entrepreneurial intentions and behaviour, allowing for critical analysis. We propose a conceptual schema of social influence that occurs in interactions among entrepreneurial individuals within business venturing and across the three stages of pre-formation, formation and growth. Our framework reconciles the conceptual classification around discovering, evaluating and exploiting entrepreneurial opportunities with the mechanisms of social influence affecting entrepreneurial behaviours. Grounded in the findings of the literature review, this framework synthesizes peer influence in entrepreneurship with the tripartite distinction of the behavioural motives recognized in contemporary theories of social influence. We suggest promising directions for further research on how interactions with peers might affect individuals’ entrepreneurial behaviours.
Keywords: systematic literature review; peer effect; peer influence; social environment; entrepreneurial behaviour; endogenous social effects; entrepreneurial process